Structural changes of the rabbit retina after 14-days tamponade of the vitreal cavity with perfluoro-organic compounds - Zhmurik , D.V.; Vit , V.V.; Dumbrova , N.E.; Molchaniuk , N.I.; Miliienko , M.V. (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Perfluoro-organic compounds (PFOC) have valuable qualities for vitreoretinal surgery and their application for short-term tamponade could expand indications for preoperative treatment and improve its results. However, there is no unambiguous opinion concerning the mechanical action of PFOC on ultrastructural structure of retina. The purpose of the study: To study the influence of 14-days PFOC tamponade on the structure of the rabbit in experiment; to compare the action of PFOC, saline solution, light and heavy silicone oil in dynamics after the tamponade completion. Material and methods. Light and electro- microscopic study was carried out on 36 rabbits (72 eyes). All animals underwent back closed subtotal vitrectomy followed by 14-days PFOC tamponade (right eye), light and heavy silicone and saline solution (left eye). The study was conducted 7, 14 and 30 days after the completion of 14-days tamponade. Results. PFOC, light and heavy silicone cause similar changes in the ultrastructure of the studied retina elements. These are mainly hydropic changes of smooth endoplasmic reticulum and mitochondria of the retinal pigment epithelium (RPE) cells, mitochondria of inner segments of photoreceptor cells, ganglion cells and Muller cells. At the same time, these cells also show the signs of compensatory-restorative processes, which is reflected in increasing of protein synthesis and energy producing activity that contributes to normalization of the revealed damage of ultrastructure. It should be noted that PFOC and light silicone have particularly similar effect on the retina, while heavy silicone causes more pronounced reaction at subcellular level. Introduction of the saline solution during the first periods of observation leads to the light reactive hydropic changes, mainly in PRE cells. Conclusion. Revealed hydropic changes in the retina after the completion of 14-days tamponade with the used substances are classified as reactive, not damaging changes and are reversible. By the end of the periods of observation the ultrastructure of the retina practically restores. Therefore PFOC can be considered as an alternative for a short-term tamponade.